Peningkatan Pengetahuan Gizi Siswa Kelas 5 SD ABATA Islamic School tentang Keamanan Makanan Jajanan - Ratnayani Ratnayani; Gusti Kumala Dewi; Vera Kasmira; Ina Ratnawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
An Elementary school (SD) children are one of the main targets of street food vendors. These snacks provide energy and some nutrients for those who consume it. However, there are things to be alert from street food, especially in terms of food safety. There are still many street food that made using food additives (colourings, sweeteners, preservatives, etc.) that do not meet the requirements. This can cause poisoning and even Extraordinary Events. Based on this, it is necessary to provide education about street food for elementary school children so that they can choose the healthy street food. Given the unfavorable situation, education is conducted online through Google Meet (Gmeet). The theme raised in this education is